2016
DOI: 10.15252/embj.201695756
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin acetylation and Wapl‐Pds5 oppositely regulate translocation of cohesin along DNA

Abstract: Cohesin is a ring-shaped protein complex that plays a crucial role in sister chromatid cohesion and gene expression. The dynamic association of cohesin with chromatin is essential for these functions. However, the exact nature of cohesin dynamics, particularly cohesin translocation, remains unclear. We evaluated the dynamics of individual cohesin molecules on DNA and found that the cohesin core complex possesses an intrinsic ability to traverse DNA in an adenosine triphosphatase (ATPase)-dependent manner. Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
140
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(156 citation statements)
references
References 75 publications
15
140
1
Order By: Relevance
“…14 Biologically, many experiments have revealed similar cohesin movement along DNA that play crucial roles in gene expression. 4,11 Nevertheless, evidences for the molecular-based correlation, either recruitment or movement along DNA, are waiting for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…14 Biologically, many experiments have revealed similar cohesin movement along DNA that play crucial roles in gene expression. 4,11 Nevertheless, evidences for the molecular-based correlation, either recruitment or movement along DNA, are waiting for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Protein crosslinking experiments at the interfaces of SMC and Scc1 subunits have also suggested that a single cohesin complex tethers replicated sister chromosomes in budding yeast cells [16,17]. In addition, single molecule observations have revealed that purified cohesin binds and diffuses along DNA as a single complex [19,20,50]. Another mechanistic explanation involves protein-protein interactions.…”
Section: Dna-dna Interactions: How To Tethermentioning
confidence: 99%
“…In budding yeast, the loader becomes dispensable for cell viability when inactivated just after, but not before, G1 phase, suggesting that the cohesin loaded onto G1 chromatin is capable of cohesion establishment. Interestingly, recent single molecule observations have suggested that the replication fork can proceed over chromatin-bound cohesin in Xenopus egg extracts [19]. …”
Section: Implications For Sister Chromatid Cohesionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo, another possible important factors affecting diffusivity of epigenetic boundaries may be the presence of insulators and architectural proteins such as CTCF and cohesins [1,44,45]. It would be interesting to adapt our model to account for these features in the future.…”
Section: Long-lived Epigenetic Domains and Boundary Diffusionmentioning
confidence: 99%